Completeness of Inpatient Medical Record Files in Obstetric and Gynecology Cases During Pandemic Period - Hadyan, Muhammad Farras; Nadjib, Mardiati (Universitas Aisyah Pringsewu, 2022)
The COVID-19 pandemic first appeared in Indonesia in March 2020, which created new problems for various public sectors. Hospitals as health care facilities are expected to provide optimal health services to patients. One of the services provided at the hospital is medical record service which is one of the determinants of the quality of health services. The incompleteness of the medical record file will cause patient documentation to become problematic and the patient's health information to be difficult to identify. Based on preliminary interviews conducted at the Taman Puring Muhammadiyah Hospital, it is known that the completeness of inpatient medical records is still low. Data obtained from the medical record unit in 2021 found that 64% of medical records were incomplete. This study uses a descriptive observational study design that identifies the percentage of completeness of medical record files where only 25.42% of inpatient medical records in obstetrics and gynecology cases are complete, this is influenced by several factors such as HR factors, supporting factors and driving factors studied. qualitatively which concludes that policy factors and the availability of SOPs, supervision from medical record officers, and the willingness of doctors affect the completeness of the contents of medical records. Abstrak: Pandemi COVID-19 muncul pertama kali di Indonesia pada bulan Maret 2020 yang menimbulkan permasalahan baru bagi berbagai sektor publik. Rumah sakit sebagai sarana pelayanan kesehatan diharapkan dapat memberikan pelayanan kesehatan yang optimal kepada pasien. Salah satu pelayanan yang diberikan di rumah sakit adalah pelayanan rekam medis yang merupakan salah satu faktor penentu kualitas pelayanan kesehatan. Ketidaklengkapan berkas rekam medis akan mengakibatkan pendokumentasian pasien menjadi bermasalah serta informasi kesehatan pasien menjadi sulit diidentifikasi. Berdasarkan wawancara pendahuluan yang dilakukan di Rumah Sakit Muhammadiyah Taman Puring diketahui bahwa masih rendahnya kelengkapan rekam medis pasien rawat inap. Data yang diperoleh dari unit rekam medis pada tahun 2021 didapatkan 64% rekam medis yang belum terisi lengkap. Penelitian ini menggunakan desain studi deskriptif observasional yang mengidentifikasi persentase kelengkapan berkas rekam medis dimana didapatkan sebesar 25,42% saja rekam medis rawat inap pada kasus obstetri dan ginekologi yang lengkap hal ini dipengaruhi dari beberapa faktor seperti faktor SDM, faktor pendukung dan faktor pendorong yang ditelaah secara kualitatif yang menyimpulkan bahwa faktor kebijakan dan ketersediaan SOP, pengawasan dari petugas rekam medis, dan kemauan dokter mempengaruhi kelengkapan isi rekam medis.